EVOLUTION OF VARIETY-JAZZ MUSIC, ITS THEORETICAL AND METHODOLOGICAL BASIS (Scientific journal of the Fergana State University, 2023)
This article discusses the historical processes of pop jazz art, the social factors that led to the emergence of popular styles in it, and their founders, skilled musicians. The work of skilled jazz performers who have contributed to the development of existing genres in the field of modern pop-jazz art is also discussed.